ChemInform Abstract: Recent Developments and Future Prospects of All‐Metal Aromatic Compounds. Issue 43 (October 2015) - Mercero, Jose M.; Boldyrev, Alexander I.; Merino, Gabriel; Ugalde, Jesus M.
Abstract Review: 135 refs.